PENGARUH PENGGUNAAN MEDIA KOLASE ANORGANIK TERHADAP HASIL BELAJAR MATA PELAJARAN SENI BUDAYA PADA SISWA KELAS IV SD NEGERI ROMANG RAPPOA - Jusnaeda; Meisar Ashari; Soekarno Buchary Pasyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The purpose of this study was to determine the work of fourth-grade students of Romang Rappoa Elementary School in using inorganic collage media and to determine the effect of inorganic collage media on the learning outcomes of art and culture subjects in fourth-grade students of Romang Rappoa Elementary School, Gowa Regency. This study used mixed methods research using the "One Group Pretest Postest Design" design. The population of this study was all fourth-grade students of Romang Rappoa Elementary School, totaling 18 people. The data collection technique used in this study was by administering pretest and posttest tests. The data collected in this study were analyzed using descriptive analysis techniques and inferential statistics, in the use of inferential statistics, T statistics (t- test) were used. Based on the results of the study using inferential data analysis using the normality test of student learning outcomes taught by applying inorganic collage media, a significant value was obtained in the pretest of 0.075, posttest 0.090 and inorganic collage 0.160. The significant value obtained was > 0.05 so that the data was normally distributed, it can be concluded that there is an influence on the learning outcomes of fourth-grade students in the arts and culture subject at Romang Rappoa Elementary School, Gowa Regency.